2016
DOI: 10.1063/1.4939772
|View full text |Cite
|
Sign up to set email alerts
|

Surface sensitivity of optical and magneto-optical and ellipsometric properties in magnetoplasmonic nanodisks

Abstract: The optical, ellipsometric, and magneto-optical surface sensitivity to dielectric environment of magnetoplasmonic nanodisks is experimentally studied. Here, the shift of the corresponding spectral structures as a function of the thickness of a coating SiO2 layer is characterized. Our results reveal that the so called pseudo-Brewster Angle, easily identified in the ellipsometric phase (Δ) spectrum, is up to four times more sensitive than the conventional features used in surface plasmon resonance based sensors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In 2015, Zubritskaya et al demonstrated that nickel dimers are able to report nanoscale distances while optimizing their own spatial orientation with about 2 orders of magnitude higher precision than current state-of-the-art plasmon rulers [66]. In 2016 Herreño-Fierro et al showed that ellipsometric phase-based transducers can be used for bio-chemical sensing purposes [127]. In 2018, Pourjamal et al showed that hybrid Ni/SiO2/Au dimer arrays display improved sensing performances if compared to random distributions of pure Ni nanodisks and/or their random counterpart [128].…”
Section: E Magneto-optical Effects In Dot-and Antidot Periodic Arraysmentioning
confidence: 99%
“…In 2015, Zubritskaya et al demonstrated that nickel dimers are able to report nanoscale distances while optimizing their own spatial orientation with about 2 orders of magnitude higher precision than current state-of-the-art plasmon rulers [66]. In 2016 Herreño-Fierro et al showed that ellipsometric phase-based transducers can be used for bio-chemical sensing purposes [127]. In 2018, Pourjamal et al showed that hybrid Ni/SiO2/Au dimer arrays display improved sensing performances if compared to random distributions of pure Ni nanodisks and/or their random counterpart [128].…”
Section: E Magneto-optical Effects In Dot-and Antidot Periodic Arraysmentioning
confidence: 99%
“…Nanoplasmonic structures, such as gratings, nanoholes, nanoparticles, etc open a way for further SPR-sensor development 6 7 8 9 . Localized surface plasmon resonances can be excited in such structures so that the electromagnetic field is concentrated in a very small area near the nanoparticle that makes localized surface plasmon resonance very sensitive to the refractive index of the surrounding media and, as a result, some localized surface plasmon resonance-based sensors showed very high sensitivity.…”
mentioning
confidence: 99%
“…Strong dependence of LSPR on the dielectric environment allows for the detection of biomolecules in MOKE or MCD measurements. 10 12 , 18 23 However, aggregates or different organic compounds that have similar dielectric permittivity are nearly indistinguishable, therefore preventing the simultaneous quantitative detection of different types of proteins or organic molecules.…”
mentioning
confidence: 99%